ANALYSIS OF METHODOLOGY AND MODELS OF STRATEGIC PLANNING OF LOCAL DEVELOPMENT IN BOSNIA AND HERZEGOVINA - Amra Abadžić (Economic Review, 2012)
The paper starts from the premise that local development policy could be seen as a tool for effective management and usage of comparative and competitive advantages in space and time. By applying the centralized administrative model in managing society andeconomy, Bosnia and Herzegovina is not capable of handling efficient development at national, regional and local level. We believethat there is a need to change the model of social and economic development, taking into consideration that so far negative effects of the erroneously applied strategies and development policies have reached unexpected limits. Strategic planning is an instrumentwhich the managers of local communities may use to make optimum decisions and their implementation. Models of strategic planningrepresent the need of local community for internationalization and attracting foreign investors, but also the appropriate public sectorsupport offered to the businesses in a particular community in order to conduct their activities in a more efficient way. Priority aims and their actual application to development of local communities are determined by strategic planning and models of strategic planning. Webelieve that an appropriately adjusted model of strategic planning provides an advantage for local communities in innovative andcooperative approaches to the problems of local government units, with the tendency for defining priority areas and sectors, whiledifferent levels of government, scientific and development institutions at local and other levels and civil sectors should be involved in solving these problems. In this paper, we focused on the presentation of models of strategic planning from the practice worldwide, as an efficient means for the implementation ofstrategic planning processes and using its positive characteristics in order to improve efficiency and effectiveness of local communities. As an example of balance between acceptance and feasibility, we showed the methodology for integrated planning oflocal development, which the local communities in Bosnia and Herzegovina seek to adopt and implement.